Reciprocal adaptation is critical in enhancing S. aureus and P. aeruginosa biofilm biomass - Xiaohan Sun; Clare M. Cooksley; Muhammed Awad; Emma F. Barry; Alkis J. Psaltis; Peter-John Wormald; Sarah Vreugde (Archives of Microbiology, 2026)
Polymicrobial communities impose a great challenge for clinical management of chronic infections. It is a consensus now that microbes exist as aggregated colonies shielded within polymeric matrix. Within this matrix more than one bacterial species can exist either in symbiotic or rival relationships. Herein, we investigated the host-specific interspecies interactions between Staphylococcus aureus and Pseudomonas aeruginosa in chronic rhinosinusitis (CRS). The indirect interaction between the two species was assessed using Transwell co-culture chambers, where S. aureus and P. aeruginosa ( n = 3 each) derived from CRS patients were cultured in separate chambers that allowed exchange of soluble factors. Later the biofilm biomass of each species was evaluated and compared to single species biofilm. Further, the influence of the co-culture conditions on antibiotic tolerance was evaluated. When derived from the same patient, co-cultured bacteria increased the biofilm biomass of each other significantly by 3.0-4.9 fold ( p p